Observational study on dry period length and its associations with milk production, culling risk, and fertility in Italian dairy farms - M. Guadagnini; P. Amodeo; F. Biscarini; A. Bolli; P. Moroni (Journal of Dairy Science, 2023)
ABSTRACT: From an initial data set involving 84,189 lactations, this research evaluated the relationship between dry period length (DPL) and milk production, culling risk, and fertility. The data set included a total of 48,297 multiparous cow lactation records, with a calving event occurring in 2019 and 2020, belonging to 62 Italian herds with at least 150 cows. The DPL was classified into 5 categories (<40, 40–49, 50–60, 61–70, and >70 d) and these categories were used to establish the association between DPL and the outcome variables. All data obtained were assessed with simple and multiple linear regressions and Cox proportional hazard models. Cumulative milk production at 60 d in milk (DIM) was the highest in DPL categories of 61 to 70 d (2,480.29 kg/cow) and 50 to 60 d (2,474.39 kg/cow), and the lowest in <40 d (2,281.29 kg/cow). Similarly, DPL categories 61 to 70 d (10,830.94. kg/cow) and 50 to 60 d (10,817.48 kg/cow) had the highest 305-d milk production, whereas the <40 d (10,200.96 kg/cow) had the lowest one. The groups with a DPL of 40 to 49 d and >70 d had slightly, but significant, lower milk production both as cumulative 60 DIM and predicted 305-d milk production. Culling risk had a curvilinear behavior, with DPL <40 d and DPL >70 d showing significantly higher odds for culling during the first 60 DIM compared with DPL of 50 to 60 d [relative risk (RR): 1.53; RR: 1.46]. Within the same comparison, DPL of 61 to 70 d also had a slightly higher risk for culling (RR: 1.13). The DPL was associated also with fertility, with DPL of 40 to 49 d and 50 to 60 d having the greatest odds for pregnancy within the first 200 DIM. The DPL of <40, 61 to 70, and >70 d were negatively associated with fertility and showed pregnancy risks of 0.87, 0.95, and 0.94, respectively. This paper reinforces the importance of DPL as we demonstrated its association with milk production, culling, and fertility. Despite being attractive for high production dairy cows, very short dry periods are at the same time also associated with higher culling risk, lower milk production and fertility. Long DPL is detrimental, especially regarding culling and fertility. In summary, reducing variability in DPL and avoiding extremes by improving reproductive performance, maximizing late lactation milk production and making wise decisions on dry-off timing, may lead to better performances and lower early culling under Italian dairy conditions.